2019
DOI: 10.2134/jeq2018.07.0271
|View full text |Cite
|
Sign up to set email alerts
|

Removing Hydrogen Sulfide Contamination in Biogas Produced from Animal Wastes

Abstract: Hydrogen sulfide (H2S) contamination in biogas produced from animal wastes limits its use to cooking and precludes it from being used for heating, lighting, or electricity generation. This limitation results in the release to the atmosphere of between 3 and 51% of total biogas produced. Biogas contains 50 to 70% methane (CH4), a potent greenhouse gas that contributes to global warming. This study aimed to develop a cost‐effective H2S filtering system using local materials rich in iron as iron oxide (Fe2O3), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In a study [91], the H 2 S removal efficiency was nearly 100% at all gas flow rates for allophane soil, brown soil and black sand, followed by typical sand (about 90-100%). This study showed that selected New Zealand soils with high iron content could potentially be used to build simple and inexpensive H 2 S adsorption beds to improve biogas quality.…”
Section: Resultsmentioning
confidence: 93%
“…In a study [91], the H 2 S removal efficiency was nearly 100% at all gas flow rates for allophane soil, brown soil and black sand, followed by typical sand (about 90-100%). This study showed that selected New Zealand soils with high iron content could potentially be used to build simple and inexpensive H 2 S adsorption beds to improve biogas quality.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to microbial processes, some chemical and physical processes in soils can remove pollutants. For example, iron-rich soils can be used to chemically remove H 2 S from the gas stream by the formation of iron sulfide [74,75].…”
Section: Managing Soils To Improve Air Qualitymentioning
confidence: 99%
“…Each filter contained one of the four types of soil (T1, T2, T3, or T4) sieved at less than 400 μm with variable mass (100 g, 150 g, or 200 g); 100 g of biochar (charcoal) dust sieved at less 350 μm; and 545 g of naturally grown moss plant collected from damp sidewalk during the rainy season. The packed bed arrangement of the substrates was adopted from Pham et al [20]; the study demonstrated removal of H 2 S using local soil materials from biogas produced by anaerobic digestion of animal wastes. In this study, 700 g layer of small and medium gravels was added above the aerator to prevent blockage by overlying filter material.…”
Section: Filter Preparationmentioning
confidence: 99%